Localization of the main immunogenic region of human muscle acetylcholine receptor to residues 67-76 of the alpha subunit. - Tzartos, S J (1988)
The majority of antibodies to the acetylcholine receptor (AcChoR), both in the human disease myasthenia gravis and in its experimental models, are directed against an extracellular area of the AcChoR alpha subunit called the main immunogenic region (MIR). We have studied the binding of anti-AcChoR monoclonal antibodies (mAbs) to 26 synthetic peptides corresponding to the hydrophilic parts of the human AcChoR alpha subunit. The binding sites for eight anti-MIR mAbs and for eight anti-alpha-subunit, non-anti-MIR mAbs were localized. Anti-MIR mAbs bound to one peptide corresponding to residues 63-80 of the human alpha subunit. A second panel of peptides corresponding to the various parts of the alpha-subunit segment 63-80 was synthesized. Anti-MIR antibodies bound to a peptide that contained the alpha-subunit sequence 67-76. Thus, a main constituent loop of the MIR is localized between residues 67 and 76 of the alpha subunit.